2013
DOI: 10.1073/pnas.1301996110
|View full text |Cite
|
Sign up to set email alerts
|

Role of caspase-1 in regulation of triglyceride metabolism

Abstract: Caspase-1 is a cysteine protease that can be activated by both endogenous and exogenous inflammatory stimuli and has been shown to have important functions in processes as diverse as proteolytic activation of cytokines, cell death, and membrane repair. Caspase-1-dependent production of the inflammatory cytokines IL-1 and IL-18 has also been implicated in the regulation of appetite, body weight, glucose homeostasis, and lipid metabolism. Consistent with the emerging views of caspase-1 in metabolic regulation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 45 publications
4
79
0
Order By: Relevance
“…Furthermore, in contrast to diet-induced obesity (Steinstra et al, 2011; McGillicuddy et al 2011), the 20 month old chow fed Il1r−/− mice did not show any improvement in glucose tolerance when compared to WT controls (Figure 1K). Notably, caspase-1 activation impairs lipid metabolism independently of IL-1 and IL-18 family of cytokines (Kotas et al, 2013). Our data suggest that during aging, reduction in Nlrp3 inflammasome induced caspase-1 activation improves glucose tolerance independently of IL-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in contrast to diet-induced obesity (Steinstra et al, 2011; McGillicuddy et al 2011), the 20 month old chow fed Il1r−/− mice did not show any improvement in glucose tolerance when compared to WT controls (Figure 1K). Notably, caspase-1 activation impairs lipid metabolism independently of IL-1 and IL-18 family of cytokines (Kotas et al, 2013). Our data suggest that during aging, reduction in Nlrp3 inflammasome induced caspase-1 activation improves glucose tolerance independently of IL-1.…”
Section: Resultsmentioning
confidence: 99%
“…It is now known that caspase-1 acts on multiple substrates including ones that control glycolysis (Shao et al, 2007) and Sirt1 which are relevant to aging and glucose homeostasis (Chalkiadaki and Guarente., 2012). Furthermore, caspase-1 is required for triglyceride clearance independently of IL-1 and IL-18 (Kotas et al, 2013). Importantly, our studies also revealed that improvement in insulin-sensitivity in Nlrp3 deficient mice is relatively late in age and that initiation of insulin-resistance is not a central event to development of degenerative disorders observed in aging.…”
Section: Discussionmentioning
confidence: 99%
“…To date, investigators have immersed themselves in searching for the key molecular targets of apoptosis. Caspase-1 is an enzyme involved in the processing of pro-IL-1β to active secreted IL-1β, which is a key inflammatory mediator driving the host response to infection [26], injury [27], and diseases [17,18]. Currently, a vast majority of the literature about caspase-1 focus on its role in inflammation, but the effect of caspase-1 on cell death has been rarely addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Given that caspase-1 functions as a regulator and effector in inflammation, metabolism [17,18], and neuronal cell death [14], we investigated the role of caspase-1 in DA neuronal degeneration in the present study. We prepared MPTP/pinduced PD mouse model so as to detect the expression of caspase-1 in the mouse midbrain.…”
Section: Caspase-1 Knockout Rescued the Loss Of Da Neurons In Mptp/p mentioning
confidence: 99%
“…52 Thus, the small level of caspase activation we observed in soleus of high-fat fed animals may not be sufficient to induce an apoptotic phenotype, but could be involved in alternative cellular functions. In fact, several caspases have metabolic roles [53][54][55] and are able to cleave enzymes involved in metabolism. 53,56 Taken together, our data suggest that HF feeding is able to induce changes to several key apoptotic signaling and regulatory factors in muscle, but not to a level that is sufficient to result in a global apoptotic phenotype.…”
Section: Discussionmentioning
confidence: 99%